Current issues in tourism, gastronomy, and tourist destination research : proceedings of the International Conference on Tourism, Gastronomy, and Tourist Destination (TGDIC 2021), Jakarta, Indonesia, 2 December 2021 /: proceedings of the International Conference on Tourism, Gastronomy, and Tourist Destination (TGDIC 2021), Jakarta, Indonesia, 2 December 2021. (2022) - Unknown
No abstract available